Pengawasan Fungsi Keimigrasian dalam Upaya Meningkatkan Pengamanan Keamanan Terpadu di Perbatasan Entikong - Mentari, Mentari; Fadilah, Nurul; Fazilah, Amira (-, 2024)
This article aims to analyze the basic functions of immigration in securing the area at the Entikong Border, so that we can see the work process in writing and what is happening in the field, especially at the Entikong Class II Immigration Office. The author uses a qualitative approach and descriptive method in describing the issues described. Data collection techniques were carried out in two ways, namely the interview process and literature study. Oversight of the Immigration function is explained through the Crucial Role of Immigration at the Entikong Border in establishing and improving integrated security in the Border area. The results of this study indicate that the performance of the Entikong Immigration Office through analysis of the Immigration function meet a fairly high standard of various forms of supervision and services can support the improvement of the quality and performance of the Entikong Immigration Office.